Colloid-mediated vertical phosphorus transport in a waste-amended soil - Grove, John H.; Matocha, Christopher J.; Makris, Konstantinos C. (My University, 2006)
Vertical phosphorus (P) transport in relatively high clay content (≥10%) soils is often assumed to be a minor contributor to surface-water P enrichment, when compared with runoff-P losses. Studies have emphasized the importance of P sorbed by colloidal particles in runoff-P losses, but little is known about the role of soil colloids on the vertical P transport in manure-amended soils. The objectives of this study were: firstly, to determine the effect of water-dispersible soil colloids (WDC) isolated from a long-term (∼ 10 years) manure-amended soil on the forms and concentrations of leached-P from manured and unmanured intact soil columns; and secondly, to evaluate whether the potential for soluble and particulate-P transport was greater in manure-amended soil columns. Around 30% of the initially added WDC concentration was detected in the effluent of both manured and unmanured columns, although WDC particle breakthrough was earlier in the manured than that of the unmanured columns. Manure-amended soil columns exhibited higher P concentrations in all P forms (MRP, particulate) when compared to the unmanured. Breakthrough curves for inorganic-particulate P (IPP) and organic-particulate P (OPP) partially explained vertical P movement with WDC. In the manure-amended soils, dissolved inorganic P (MRP) concentrations were reduced in the presence of WDC relative to the untreated (no WDC added), but did not reduce MRP concentrations to levels observed with the unmanured columns. Iron-hydroxide-rich WDC particles exhibited similar breakthrough with particulate P and suggested an iron-phosphate association in the transported WDC fraction of the soil. Not only do naturally occurring WDC act as P carriers, but upon saturation of their P sorption sites are unable to reduce MRP “leaking” in long-term manured soils. Results illustrated the soluble and particulate P vertical transport through a waste-amended soil.
Keywords: WDC; Water-dispersible soil colloids; MRP; Molybdate reactive P; IPP; Inorganic-particulate P; OPP; Organic-particulate P; BTC; Breakthrough curve